Optimization of vertical well completion in a saturated reservoir with bottom water drive for maximizing recovery. Issue 3 (4th May 2019) - Kumar, Manish; Sharma, Pushpa; Gupta, D. K.
ABSTRACT: To maximize oil recovery from a bottom water drive reservoir using a vertical well, estimation of transition zone thickness and determination of critical rate are very important. To augment or sustain the oil production and recovery rate, it is necessary to place the well using proper offset from water/oil contact (WOC) and assign a proper liquid rate. The objective of this paper is to establish a development strategy for a bottom water drive reservoir which will maximize the oil production. Analytical methods are first used to find initial approximations of critical production rate, then comprehensive numerical investigation of the relevant parameters affecting water coning behavior is studied using a history matched, corner point gridding three-dimensional reservoir simulation model. Additionally, core and log data were analyzed to determine WOC and transition zone thickness. Establishment of well placement with proper offset from WOC and rate has been carried out in a history matched three-dimensional model. Better understanding of the reservoir in terms of saturation height function (thickness of the transition zone) and performing rate sensitivity at various offsets from WOC has enabled us to place the well at an optimum point and drain the reservoir in an efficient manner.